Effects of four months of periodized aquatic exercise program on functional autonomy in post-menopausal women with parkinson's disease (Efecto de cuatro meses de entrenamiento de ejercicio acuático periodizado sobre la autonomía funcional en mujeres posm - Hall López, Javier Arturo; Ochoa Martínez, Paulina Yesica; Lara Monzon, Cristhian Obed; Gomes de Souza Vale, Rodrigo (Retos, 2018)
Objective: To determine the effect of a periodized aquatic exercise program on functional autonomy in post-menopausal women with Parkinson's disease. Methods: Nine post-menopausal women diagnosed with idiopathic Parkinson's disease, with stage I-III according to Hoehn and Yahr scale, (age 60.4 ± 3.87 years) participated in the 16-week of periodized aquatic exercise program five times a week, 30 minutes of aquatic exercise with work heart rate reserve of 40-50% (1-8th week) increasing the load to 50-60% (9-16th week. The protocol of the Group of Latin-American Development for Maturity (GDLAM) was used to evaluate functional autonomy; As statistical analyses student T test for paired samples was used, also percent changes (Δ %) were calculated, the results showed significant improvement (p